2023
DOI: 10.1007/s00592-023-02097-w
|View full text |Cite
|
Sign up to set email alerts
|

Glucose variability: a new risk factor for cardiovascular disease

Abstract: Aims and data synthesis Glucose variability (GV) is increasingly considered an additional index of glycemic control. Growing evidence indicates that GV is associated with diabetic vascular complications, thus being a relevant point to address in diabetes management. GV can be measured using various parameters, but to date, a gold standard has not been identified. This underscores the need for further studies in this field also to identify the optimal treatment. Conclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…CVDs are the leading cause of morbidity and mortality in patients with diabetes; therefore, the prevention of cardiovascular (CV) complications is essential in the treatment of T2DM [32]. In recent years, there has been an expansion of the armamentarium for T2DM treatment with drugs that are not limited exclusively to glycemic control but also have positive effects on reducing CV risk.…”
Section: Glp-1ras and Reduction In Cardiovascular Riskmentioning
confidence: 99%
“…CVDs are the leading cause of morbidity and mortality in patients with diabetes; therefore, the prevention of cardiovascular (CV) complications is essential in the treatment of T2DM [32]. In recent years, there has been an expansion of the armamentarium for T2DM treatment with drugs that are not limited exclusively to glycemic control but also have positive effects on reducing CV risk.…”
Section: Glp-1ras and Reduction In Cardiovascular Riskmentioning
confidence: 99%
“…Emerging research indicates that GV is an independent risk factor for diabetes mellitus (DM) complications, particularly in predicting cardiovascular risks [ 5 ]. Further investigations have established a correlation between acute GV and the severity and prognosis of various diseases, extending beyond DM [ 6 ] to encompass critically ill patients [ 7 ] and cardiovascular conditions [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Glycemic variability, oscillations in blood glucose levels, refers to the measurement of fluctuations in glucose or other related parameters of glucose homeostasis over a specific time period [9]. An elevated glycemic variability can contribute to the activation of oxidative stress, impairment of endothelial function, and glycosylation of proteins [10][11][12]. The findings of previous studies have demonstrated a positive correlation between glycemic variability and mortality in critically ill patients, including those with subarachnoid hemorrhage and sepsis [13,14].…”
Section: Introductionmentioning
confidence: 99%